Effects of late-summer prescribed fire on botanical composition, soil cover, and forage production in Caucasian bluestem-infested rangelands in the Kansas Smoky Hills - Giefer, Helen Patricia (Kansas State University, 2024)
The invasive old-world bluestem species, yellow bluestem (Bothriochloa ischaemum) and Caucasian bluestem (Bothriochloa bladhii), have been displacing native grasses and forbs in the Great Plains since they were first introduced to the United States for soil conservation and as a forage source in the early 20th century. Targeted removal of old-world bluestems has proven difficult. Traditional, spring-season prescribed fire appears to promote growth and proliferation of the invasive species to a greater extent than native species; moreover, treatment with glyphosate is expensive and non-selective. After reports of successful yellow bluestem removal using late-summer prescribed fire, a similar experiment targeting Caucasian bluestem was conducted in a heavily invaded, mixed-grass pasture in Ellsworth County, Kansas. Eighteen 4,047 square meters (i.e., 1 acre) plots were assigned randomly to one of three treatments: no burn (control), one burn (August 14, 2019), or two burns (August 14, 2019, and August 11, 2021). Beginning in 2019 and ending in 2023, annual measurements of soil cover, botanical composition, forage biomass, and Caucasian bluestem frequency were conducted in each plot. In plots burned once or twice, bare soil increased (P < 0.01) and Caucasian bluestem cover decreased (P < 0.01) the year following each fire, allowing for increases in forb cover (P = 0.03) and grass species richness (P = 0.01). While C₄ tallgrass and shortgrass covers were not affected by fire (P ≥ 0.13), C₄ midgrasses, of which Caucasian bluestem is a member, decreased (P = 0.04) in response to fire. These results were interpreted to suggest that late-summer prescribed fire may provide targeted Caucasian bluestem control without inflicting harm on native vegetation; however, it is believed that fire must be regularly applied to maintain control over time.
Keywords: Bothriochloa bladhii; Caucasian bluestem; Invasive plants; Mixed-grass prairie; Old-world bluestem; Prescribed fire